(untitled) (Journal of Applied Learning and Teaching, 2024)
Amidst international challenges in teacher recruitment and retention, understanding how best to prepare pre-service teachers for professional practice is of the utmost importance. Managing pupil behaviour is of particular concern due to a rise in reported challenges experienced by teachers following the COVID-19 pandemic, with consequences for the wellbeing of teachers and pupils, as well as for teacher retention. Simulation-based learning (SBL) within Immersive Virtual Reality (IVR) environments provides a means by which pre-service teachers can be supported to develop essential skills in a safe, supportive environment. However, the use of SBL for Initial Teacher Training (ITT) remains in its infancy, with few previous studies in this field of enquiry. In addressing these issues, this research protocol proposes to target pre-service teachers undergoing an ITT programme in a realist evaluation to further understand how they embrace behaviour management strategies in an IVR environment. Adopting a sequential mixed-method approach, we plan to collect qualitative and quantitative data with stakeholder groups in the development of a holistic evaluation framework. Our intended outcomes are to synthesise data to explore the key factors needed to design, implement, and evaluate IVR within SBL approaches to better understand their potential as a form of professional learning.